Faktor Yang Mempengaruhi Respon Petani Terhadap Program Gerakan Tanam Cabai Di Kelompok Tani Kerapu Makmur Kelurahan Berkas Kota Bengkulu - Oktrada, Darty; Fariadi, Herri; Nurmalia, Ana (Jurnal Multidisiplin Dehasen (MUDE), 2025)
The Chili Planting Program in Berkas Village which was implemented in 2023 to increase national chili productivity. The purpose of this research was to determine the response of farmers to the chili planting movement program and to analyze the factors that influence farmers' responses to the chili planting program in the Kerapu Makmur Farmers Group, Berkas Village. This research was conducted from August 1 to August 30, 2024. The population in this research was 30 people and was analyzed using a Likert scale. This research method uses descriptive analysis and multiple linear analysis. The results of the research showed that the farmer's response to the chili planting program in the Kerapu Makmur Group, Berkas Village, Teluk Segara District, Bengkulu City was in the moderate category (39.3) Factors that influence farmers' responses to the chili planting . Are Number of Family Members, Frequency of attending counseling and Cohesiveness in the group. While those that do not have an effect are age, gender, education, farming experience, and household income of chili farmers in the Kerapu Makmur farmer group, Berkas Village, Teluk Segara District, Bengkulu City